Research Brief: The Teen ADHD Workshop to Improve Adolescent ADHD Treatment Engagement. Issue 8 (June 2020) - Schoenfelder, Erin; McCabe, Connor; Fife, Aurora; Herzig, Lisa; Ahrens, Kym
Objective: Adolescents with ADHD are at risk of functional problems that may be mitigated by consistent ADHD treatment. This study pilots a brief intervention for adolescents with ADHD and their parents to increase treatment knowledge and family motivation to seek treatment.Method: The 3-hr curriculum was developed by a multidisciplinary team and included psychoeducation, goal setting, and motivational interviewing. Fifteen adolescents and 20 caregivers participated in the workshop, completed pre- and post-test assessments, and reported on acceptability.Results: Acceptability and satisfaction with the intervention were high. Perceived knowledge of ADHD increased post intervention; stigma was unchanged. Parents reported more acceptability of stimulant medications and less willingness to use special diets or cognitive games. Family feedback informed modifications to the curriculum.Conclusion: The Teen ADHD Workshop is a feasible and acceptable intervention to increase knowledge of ADHD and evidence-based treatments. Further research will evaluate effects on treatment participation.